PELUANG PENERAPAN PRODUKSI BERSIH PADA KAWASAN INDUSTRI PERIKANAN MUNCAR KABUPATEN BANYUWANGI JAWA TIMUR - Widodo, Lestario (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Coastal areas in Muncar Banyuwangi has developed one of the largest fisherys industryÃ‚Â centers in Indonesia. Fisherys industry in the production process using a fish as a mainÃ‚Â input and also need a lot of clean water. The impact of these activities is the occurrenceÃ‚Â of environmental pollution in the form of liquid waste and the unpleasant smell. CleanerÃ‚Â produktion is minimization of waste from source. The application of cleaner productionÃ‚Â with its assessment and identification to production process will create any innovations. In the cleaner production method contains several strategies that can be implemented forreducing and minimizing of industrial waste including prevention, recycling, treatment andÃ‚Â disposing. One of prospective instruments that can be developed further in the industrialÃ‚Â implementation of cleaner production is fisherys industry at Muncar Banyuwangi. The mainÃ‚Â opportunities to implementation of cleaner production, especially in stages using excessiveÃ‚Â water in the process of weeding and cleaning fish, stage of the main raw material the use ofÃ‚Â fish by re-sorting a more effective, and efficient charging process scattered on the tin.Key words : Cleaner production, fisherys industry